'n Dialogiese kommunikasieteorie vanuit 'n Prakties-Teologiese perspektief - Pieterse, Hendrik J. C. (Verbum et ecclesia, 1988)
A dialogical theory of communication from a practical theological perspective For our practical theological reflection on the communication of the gospel in ministry, we need a sound theory of communication. We choose for a dialogical theory of communication which suits the nature of Christian communication. This theory is developed with insights from theology and philosophy. The roots of a dialogical theory of communication are found in the thoughts of Socrates, Plato en Augustine. Kierkegaard is seen as the founder of the modern dialogical theory of communication, whilst the contributions of Buber, Jaspers, Gadamer and Habermas are traced. In an era of mass communication and propaganda, Christians need a communicative context where dialogue, freedom and an existential experience of God's love and grace can develop.